2013
DOI: 10.1103/physreve.87.032128
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of hard asymmetric dumbbell particles

Abstract: Using Monte Carlo simulations and free energy calculations, we study the phase behavior of hard asymmetric dumbbell particles with a constituent sphere diameter ratio of 0.5. We find a rich phase behavior with isotropic fluid, rotator, and periodic NaCl-based and both periodic and aperiodic CrB-based crystalline phases. The rotator phases found to be stable in this study are similar to those found in systems of snowman-shaped and dumbbell particles and we investigate the behavior of these phases by comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…A variety of shapes in bulk and under the influence of external fields have been explored including spherocylinders [15][16][17][18] , cut-spheres 23 [24][25][26][27][28] , dimers [29][30][31] , bowl-like particles [32][33][34] , concave spherical caps [35][36][37] , polyhedra [38][39][40][41][42] , and a variety of branched particles [43][44][45][46] , just to mention few examples. An assumption behind these studies is that the effect of gravitational forces is negligible, corresponding to a situation of colloidal particles embedded within a density matched (implicit) medium.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of shapes in bulk and under the influence of external fields have been explored including spherocylinders [15][16][17][18] , cut-spheres 23 [24][25][26][27][28] , dimers [29][30][31] , bowl-like particles [32][33][34] , concave spherical caps [35][36][37] , polyhedra [38][39][40][41][42] , and a variety of branched particles [43][44][45][46] , just to mention few examples. An assumption behind these studies is that the effect of gravitational forces is negligible, corresponding to a situation of colloidal particles embedded within a density matched (implicit) medium.…”
Section: Introductionmentioning
confidence: 99%
“…This work offers various directions for future research. Firstly, the presented Stöber/MPTMS* hetero-dimers of precisely controlled aspect ratio are of interest for self-assembly, allowing to experimentally explore phase diagrams of such snowmenshaped particles [71] in great detail, because of the precisely controlled shape and the ability to label the two compartments with different fluorescent dyes. By further concentrating on the synthesis of MPTMS*/MPTMS* particles close to the transition from snowman-shaped particles to engulfed-spheres, precisely controlled snowman-shaped particles homogeneously composed of MPTMS* may also be created.…”
Section: Discussionmentioning
confidence: 99%
“…A dumbbell can be seen as a dimer of two spheres and is hence comprised by two lobes of diameters σ 1 and σ 2 permanently bonded at a fixed bond length l. Despite the system being formed by simple spherical lobes, dumbbells with different degree of convexity exhibit the formation of unusual structures due to the additional orientational degrees of freedom (absent in single spheres). [58][59][60][61][62] For example, computer simulations of hard homonuclear dimers, i.e., dumbbells formed by two tangent spheres with σ = σ 1 = σ 2 , are known to pack at high densities in a way similar to that of monodisperse spherical particles. However, the configurational degeneracy arising from the large number of possible arrangements of the particle bonds within the crystal lattice promotes the formation of aperiodic crystals 63,64 .…”
Section: Hard and Soft-core Models Of Non-convex Particlesmentioning
confidence: 99%
“…Such an intermediate state exhibits shear banding at a local level, and a hexatic-like behavior at the macroscopic level. For dumbbells with different lobe diameters and bond lengths, computer simulation studies using Monte Carlo simulation and free energy calculations have shown that the particles can exhibit a very rich phase behavior ranging from plastic crystals to aperiodic crystals, and aligned crystals 61,62,70 Changing the chemistry and the morphology (roughness) of one of the lobes of a dimer can also be used to target preferential interactions through the addition of depletants. This approach of controlling the interparticle interaction was demonstrated by Kraft and co-workers in a combined experimental and simulation study of asymmetric dimers comprised by one smooth lobe and one highly rough lobe 71 .…”
Section: Hard and Soft-core Models Of Non-convex Particlesmentioning
confidence: 99%